A Histological Study of Some Important Visceral Organs for Estimating Time Since Death (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Histological changes following death follow a characteristic fixed pattern and these can be  utilized to estimate time since death within a definite time brackets as is reflected by a high  percentage of positive cases conforming to definite brackets. A clear-cut approximation in time  brackets following death can be arrived at with some adjustment for seasonal variations. In the  present study, histological changes occur much earlier than reported by earlier workers in the  field. Moreover, histological changes in the visceral organs (heart and liver) may offer an  improvement over other conventional methods for estimating time since death.
Keywords: positive; Histological